2020
DOI: 10.1111/tpj.14688
|View full text |Cite
|
Sign up to set email alerts
|

Plant species‐specific recognition of long and short β‐1,3‐linked glucans is mediated by different receptor systems

Abstract: SummaryPlants survey their environment for the presence of potentially harmful or beneficial microbes. During colonization, cell surface receptors perceive microbe‐derived or modified‐self ligands and initiate appropriate responses. The recognition of fungal chitin oligomers and the subsequent activation of plant immunity are well described. In contrast, the mechanisms underlying β‐glucan recognition and signaling activation remain largely unexplored. Here, we systematically tested immune responses towards dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 103 publications
1
73
0
Order By: Relevance
“…Bacterial EPS is only one group of such carbohydrates. Another example is short-chain and long-chain beta-glucans of bacterial or fungal origin, some of which have been shown to elicit responses in many plants 26 , 27 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial EPS is only one group of such carbohydrates. Another example is short-chain and long-chain beta-glucans of bacterial or fungal origin, some of which have been shown to elicit responses in many plants 26 , 27 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In A. thaliana, the six-monomer β-1,3-glucan laminarihexaose is perceived by pattern-recognition receptors belonging to the LysM family: CHITIN ELICITOR RECEPTOR KINASE 1 (CERK1), LYSIN MOTIF-CONTAINING RECEPTOR-LIKE KINASE 4 (LYK4), and LYK5 [119] ( Figure 1B). In contrast, in the case of Nicotiana benthamiana, the equivalent LysM pattern-recognition receptors were not required to detect β-1,3-glucan oligosaccharides [120].…”
Section: Perception Of Cell Wall Damage: Wall-derived Damage-associatmentioning
confidence: 88%
“…Therefore, callose-derived oligosaccharides can be considered to be both DAMPs and fungal elicitors. Recently it was shown that β-1,3-linked glucans of different degree of polymerization are indeed perceived by both monocots and dicots, activating different immunity responses [119,120]. In A. thaliana, the six-monomer β-1,3-glucan laminarihexaose is perceived by pattern-recognition receptors belonging to the LysM family: CHITIN ELICITOR RECEPTOR KINASE 1 (CERK1), LYSIN MOTIF-CONTAINING RECEPTOR-LIKE KINASE 4 (LYK4), and LYK5 [119] ( Figure 1B).…”
Section: Perception Of Cell Wall Damage: Wall-derived Damage-associatmentioning
confidence: 99%
“…Recent work has demonstrated that LysM‐PRRs are involved in the perception by plants of 1,3‐β‐glucans isolated from fungal cell walls (Mélida et al ., 2018; Wanke et al ., 2020b). Specifically, the hexasaccharide 1,3‐β‐ d ‐(Glc) 6 (laminarihexaose) is an immune‐active structure whose recognition in Arabidopsis is CERK1‐dependent.…”
Section: Introductionmentioning
confidence: 99%